Anisotropic fatigue properties of Alloy 718 manufactured by Electron Beam Powder Bed Fusion. (December 2020) - Balachandramurthi, Arun Ramanathan; Moverare, Johan; Hansson, Thomas; Pederson, Robert
Highlights: LCF behaviour of post-treated EB-PBF Alloy 718 is anisotropic. Parallel direction has better LCF performance than transverse direction. Strain vs. life relationship is not affected by post-treatments. Pseudo-elastic stress vs. fatigue life approach can potentially handle anisotropy. Abstract: In this study, Alloy 718 specimens manufactured by Electron Beam Powder Bed Fusion process are subjected to two different post-treatments to have different microstructural features. Low cycle fatigue testing has been performed both parallel and transverse to the build direction. EB-PBF Alloy 718 exhibits anisotropic fatigue behaviour; the fatigue life is better along the parallel direction compared to the transverse direction. The anisotropy in fatigue life is related to the anisotropy in the Young's modulus. The pseudo-elastic stress vs. fatigue life approach is presented as a potential solution to handle anisotropy in fatigue life assessment of additively manufactured engineering components.